Behavioral responses underpinning resistance and susceptibility of honeybees to Tropilaelaps mercedesae - Khongphinitbunjong K. (2014)
Behavioral responses of Apis cerana, Apis dorsata, and Apis mellifera to the ectoparasitic mite, Tropilaelaps mercedesae, were compared using two laboratory bioassays: cohorts of 50 caged worker bees and individual-caged worker bees, all of unknown ages. For the group bioassays, ten T. mercedesae were placed on the bodies of bees in each cohort. After 6 h, nearly 2/3 of the mites placed on A. cerana had fallen from the bees onto sticky traps that were placed under the cages, compared to only about 1/3 for A. dorsata and A. mellifera. The majority of fallen mites fell within 24 h from A. cerana (93.3 ? 2.3%), 36 h from A. dorsata (92.2 ? 1.9%), and 48 h from A. mellifera (91.3 ? 1.4%). Higher proportions of injured mites were observed among the mites that fell from A. cerana (38.3 ? 12.9%) and A. dorsata (33.9 ? 17.4%) than among those that fell from A. mellifera (19.5 ? 7.2%). The rapid fall of mites from the bodies of A. cerana may be due to a combination of auto-grooming and rapid body shaking of the bees. In individual bee assays, where individual bees were challenged with one female T. mercedesae, A. cerana and A. dorsata exhibited faster behavioral responses to the presence of mites than did A. mellifera (39.4 ? 13.2, 44.9 ? 19.2, and 188.4 ? 63.9 s, respectively). Phoretic T. mercedesae were mostly observed attaching to the propodeum/petiole region of all three bee species, although some mites also occupied the wing base area of A. dorsata and A. mellifera. ? 2012 INRA, DIB and Springer-Verlag, France.